2004
DOI: 10.1186/bcr931
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight, parental age, birth order and breast cancer risk in African-American and white women: a population-based case–control study

Abstract: Introduction Much recent work has focused on hypotheses that very early life exposures influence adult cancer risk. For breast cancer it has been hypothesized that high in utero estrogen exposure may increase risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
52
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 46 publications
(76 reference statements)
3
52
1
2
Order By: Relevance
“…Most studies find evidence of a positive association between birth weight and breast cancer risk, but several have not (Ekbom et al, 1997;Sanderson et al, 1998Sanderson et al, , 2002Titus-Ernstoff et al, 2002;Hodgson et al, 2004). Although not associated overall in our data, risk was elevated, albeit not statistically significantly, with high birth weight in younger women consistent with previous observations (Michels et al, 1996;Sanderson et al, 1996;De Stavola et al, 2000;Innes et al, 2000;Mellemkjaer et al, 2003;McCormack et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Most studies find evidence of a positive association between birth weight and breast cancer risk, but several have not (Ekbom et al, 1997;Sanderson et al, 1998Sanderson et al, , 2002Titus-Ernstoff et al, 2002;Hodgson et al, 2004). Although not associated overall in our data, risk was elevated, albeit not statistically significantly, with high birth weight in younger women consistent with previous observations (Michels et al, 1996;Sanderson et al, 1996;De Stavola et al, 2000;Innes et al, 2000;Mellemkjaer et al, 2003;McCormack et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…Only one investigated the interaction of birth weight and education (Titus-Ernstoff et al, 2002), reporting a stronger association of high birth weight with breast cancer risk in women whose fathers were the most educated. As discussed elsewhere (Hodgson et al, 2004), most studies have been conducted in Caucasians from high-risk populations. Results from studies in a relatively disadvantaged population in the US (Hodgson et al, 2004) and in Chinese women with limited education (Sanderson et al, 2002) suggest an inverse association of birth weight and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, birth order has been associated with birth weight, a risk factor for breast cancer (Juntunen et al, 1997;Potischman and Troisi, 1999;Barba et al, 2006). In utero estradiol levels decrease with birth order, with potential implications for risks of breast, testicular and possibly other cancer sites (Bernstein et al, 1986;Panagiotopoulou et al, 1990;Trichopoulos, 1990;Hsieh et al, 1991;Prener et al, 1992;Westergaard et al, 1998;Potischman and Troisi, 1999;Petridou et al, 2000;Weir et al, 2000;Hodgson et al, 2004;Richiardi et al, 2004;Sorensen et al, 2005). Family crowding necessarily involves intimate contacts between its members, with potential effects on infectious diseases (Kinlen et al, 1990;Altieri et al, 2006a, b).…”
mentioning
confidence: 99%
“…The other three studies showed no association with maternal age (Hemminki et al, 1999;HilakiviClarke et al, 2001;McCormack et al, 2003). Of the 14 case -control studies, 5 report a significant positive association between maternal age and breast cancer (Rothman et al, 1980;Janerich et al, 1989;Thompson and Janerich, 1990;Innes et al, 2002;Hodgsen et al, 2004), 3 studies report a non-significant positive association (Ekbom et al, 1997;Choi et al, 2005;Park et al, 2006) and 6 studies do not find an association between maternal age and breast cancer risk (Le Marchand et al, 1988;Sanderson et al, 1996;Newcomb et al, 1997;Weiss et al, 1997;Titus-Ernstoff et al, 2002;Mellemkjaer et al, 2003). Reasons for the inconsistencies in results may include the variety in study designs or study populations.…”
Section: Discussionmentioning
confidence: 99%